(untitled) (Global Journal of Management and Business Research, 2019)
It is necessary to mention that the accounting thought has evolved enough during the XX and XXI centuries, but this evolution has been given to chance through semiotic mediationsand not as a reaction to conscious efforts to perfect and invigorate a methodology. The mechanism of book keeping in accounting represents an abstract mathematical system whose validity depends more on its logical coherence tan on empirical understanding. It would be advisable to extend or rectify this model, or create new and complementary ones based on the new existing mathematical models. However, this abstract system generates another problem: The Accountant must decide which mathematical model most appropriately reflects a specific situation where the economy, administration, accounting and finance are involved. If the accounting propositions are expressed with symbols, it will be easier to adapt and integrate them to the theoretical propositions of the domain of the disciplines.